Decreasing Error in Functional Hip Joint Center Calculation using Ultrasound Imaging - Upadhyaya, Swati (Université d'Ottawa / University of Ottawa, 2013)
The hip joint center (HJC) is needed for calculation of hip kinematics in various applications. In the functional method, the center is determined by moving femur with respect to acetabulum. A popular way for measuring this movement is through an optical motion capture system. This method is fast and economical for most applications where we require an instant HJC even though the reconstruction error in bone position calculation exists due to skin artifact. This error is caused by movement of markers placed on skin rather than on actual bone. Here we introduce ultrasound imaging as an additional modality to measure the change in soft tissue thickness above bone while hip is flexed. We use this information on the tissue thickness change to recalculate position of markers placed on skin to match the movement of bone. A good advantage of using ultrasound machine is its non-invasiveness. We calculated HJC using a symmetric center of rotation estimation (SCoRE) algorithm, which uses the concept of coordinate transformation on 3D marker position data. The algorithm gives the 3D position of two centers, one for each hip bone. The distance between these two centers (SCoRE residual) gives us a hint on the accuracy of the HJC calculation and has been proved to be proportional to the error with respect to actual center in previous studies. These two centers should ideally coincide as they collectively form a spherical joint. Our new algorithm for HJC calculation with tissue thickness compensation, measured using ultrasound imaging shows the error has been reduced from 9.13 mm to 4.87 mm
Keywords: Functional Hip Joint Center; Ultrasound